Peran Teknologi Pendidikan Dalam Pembelajaran - Metodius Bate’e; Dermawan Zebua (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The rapid development of information technology in the era of globalization has brought significant changes to various aspects of life, including education. Technology not only functions as an aid but also becomes an integral part of the learning process, improving the quality, effectiveness, and flexibility of learning. This study aims to provide educators, particularly elementary school teachers, with an understanding of the importance of technology in the learning process and to encourage the appropriate integration of technology into teaching activities. The method used in this study is a literature study by analyzing various relevant literature sources related to educational technology and education policy in Indonesia. The results of the study indicate that the application of educational technology can create more interactive, creative, and student-centered learning, and support the development of 21st-century skills. Furthermore, the Freedom to Learn policy serves as an important foundation in encouraging educational transformation that is adaptive to technological developments. Thus, the planned and systematic use of educational technology is expected to improve the quality of learning and contribute to the development of superior and sustainable human resources.